The impact of dietary sn-2 palmitic triacylglycerols in combination with docosahexaenoic acid or arachidonic acid on lipid metabolism and host faecal microbiota composition in Sprague Dawley rats. Issue 5 (26th April 2017) - Wan, Jianchun; Hu, Songyou; Jacoby, Jörg J.; Liu, Jie; Zhang, Yaqiong; Yu, Liangli (Lucy)
Abstract : Dietary fat altered lipid metabolism and host faecal microbiota in rats. Abstract : Sn-2 palmitic acid triacylglycerols (sn2PA fat) and polyunsaturated fatty acids are thought to influence the metabolic status and intestinal bacterial population of the host. In this study, the impact of sn2PA fat in combination with DHA or ARA in the diet on lipid metabolism in the liver and faecal microbiota composition were investigated in rats fed diets containing sn2PA fat, 90% sn2PA fat + 10% DHA oil (wt%), or 90% sn2PA fat + 10% ARA oil (wt%). Tissue fatty acid composition was measured using gas chromatography (GC), whereas the faecal microbial composition was assessed using 16S rRNA high-throughput sequencing technology. In addition, faecal short-chain fatty acids (SCFA) were analyzed using ion chromatography. The results showed that sn2PA fat in combination with DHA or ARA significantly reduced liver triacylglyceride (TG) content compared with the sn2PA fat only group. Moreover, the supplementation with sn2PA fat in combination with DHA or ARA significantly promoted the growth of Lactobacillus in the feces at the genus level. On the other hand, the growth of the opportunistic pathogen Desulfovibrio was significantly inhibited by sn2PA fat in combination with ARA compared with the sn2PA fat group. In addition, sn2PA fat in combination with DHA or ARA significantly increased total SCFA concentration in the faeces, suggesting a beneficial effect on host intestinal health.